Analysis of the clinical pharmacy service in a university hospital - Cruz, Lucas Taffarel (2020)
Introduction: Patient safety is one of the main study targets today, in several segments in the health field. Drug-related problems (DRP) stand out among the most commonly committed in health services. The pharmacist's role in the clinical pharmacy is established as a service that contributes to the optimization of hospital care by improving the quality of pharmacotherapy, minimizing drug-related problems. Objective: To identify and quantify the DRP and pharmaceutical interventions found in the Pharmacy Service of the University Hospital of the Federal University of Juiz de Fora (HU-UFJF) and also present the acceptance rates of pharmaceutical interventions according to the acceptability of the health team. Material and Methods: A retrospective observational study was carried out at HU-UFJF of the results obtained by the clinical pharmacy service from April to October 2018. Results: 18.795 prescriptions were evaluated and 2.834 PRM were found and considered. The most prevalent type of drug-related problem was dilution and/or infusion rate corresponding to 28.7%. Conclusion: The clinical pharmacy service detected several problems related to drug use, which led to opportunities for improvement in pharmacotherapy, contributing to patient safety.